Kant on Eating and Drinking - Borges, Maria (Con-Textos Kantianos. International Journal of Philosophy, 2021)
In this paper I analyze Kant’s ideas about eating and drinking. First, I show that gluttony and drunkenness are considered ways to oppose to the duty to oneself as an animal being. Second, I claim that for Kant there is a healthy way of having meals, which consists in eating together with friends. Then I indicate that Kant accepts that one can drink at dinner parties but has to avoid drinks that lead to drunkenness and unsocial behavior. In this sense, he draws a classification of the various kinds of alcoholic drinks, according to their potential harm. Afterwards, I illustrate how Kant’s own intimate life was a daily practice of his thoughts on dietetic conceptions and on what is better for digestion and health. To conclude, I mention the idea of a philosopher’s medicine of the body and why a strict diet should be avoided.